THE ROLE OF MEDIA AND GAME OF TRP - Sharma, Minakshi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The media, which is the fourth pillar of democracy, is crucial in influencing public opinion. People rely heavily on the media to raise their awareness and engage with the government. However, a few negative concepts also exist that cast doubt on the veracity of media reports. One of these is the TRP race. The race of TRP and the bad features of media trials have risen as a result of media organizations becoming more private. In most of these countries, privatization began spontaneously and was only later subject to government regulation. Eventually, the state or other public funds either took ownership of the media or sold them off. In other words, in countries where the media was socially owned, state-controlled media turned became state-owned media. For the media to adequately carry out its responsibilities, TRP should be regulated by appropriate regulation.